Quantified Ataxic Breathing Can Detect Opioid-Induced Respiratory Depression Earlier in Normal Volunteers Infused with Remifentanil - Farney, Robert J; Johnson, Ken B; Ermer, Sean C; Orr, Joseph A; Egan, Talmage D; Morris, Alan H; Brewer, Lara M (Anesthesia and analgesia, 2025)
Ataxic breathing (AB) is a well-known manifestation of opioid effects in animals and humans, but is not routinely included in monitoring for opioid-induced respiratory depression (OIRD). We quantified AB in normal volunteers receiving increasing doses of remifentanil. We used a support vector machine (SVM) learning approach with features derived from a modified Poincaré plot. We tested the hypothesis that AB may be found when bradypnea and reduced mental status are not present. Twenty-six healthy volunteers (13 female) received escalating target effect-site concentrations of remifentanil with a low baseline dose of propofol to simulate typical breathing patterns in drowsy patients who had received parenteral opioids. We derived respiratory rate (RR) from respiratory inductance plethysmography, mental alertness from the Modified Observer's Assessment of Alertness/Sedation Scale (MOAA/S), and AB severity on a 0 to 4 scale (categories ranging from none to severe) from the SVM. The primary outcome measure was sensitivity and specificity for AB to detect OIRD. All respiratory measurements were obtained from unperturbed subjects during steady state in 121 assessments with complete data. The sensitivity of AB for detecting OIRD by the conventional method was 92% and specificity was 28%. As expected, 69 (72%) of the instances not diagnosed as OIRD using conventional measures were observed to have at least moderate AB. AB was frequently present in the absence of traditionally detected OIRD as defined by reduced mental alertness (MOAA/S score of <4) and bradypnea (RR <8 breaths/min). These results justify the need for future trials to explore replicability with other opioids and clinical utility of AB as an add-on measure in recognizing OIRD.